2022
DOI: 10.30541/v44i4iipp.597-614
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Relationship between Poverty, Population Growth, and Environment

Abstract: Deterioration of natural resources during the past few decades has come to prominence as one of the most important current global issues [Desta (1999)]. Increase in population density in ecologically fragile areas and consumption of nonrenewable natural resources at high rates is seen as one of the leading causes of this deterioration [Grigg (1991)]. At present, in some of the developing countries, the pollution of air, water and soil has reached life-threatening levels [Gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…The birth rate has the tendency to be high, linked to the high rate of poverty, and so a continued high proportion of the population will continually live in poverty. 35,37,47 This postulation justified the inclusion of population growth rate in equation 1and as argued in the Solow Growth model. The results in this study show that an increase in the population growth rate results in an increase in the rate of poverty (because more people tend to chase fewer resources) by 93.4 percent, 45.9 percent, 10.1 percent and 22.6 percent respectively, as shown in the Appendices.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The birth rate has the tendency to be high, linked to the high rate of poverty, and so a continued high proportion of the population will continually live in poverty. 35,37,47 This postulation justified the inclusion of population growth rate in equation 1and as argued in the Solow Growth model. The results in this study show that an increase in the population growth rate results in an increase in the rate of poverty (because more people tend to chase fewer resources) by 93.4 percent, 45.9 percent, 10.1 percent and 22.6 percent respectively, as shown in the Appendices.…”
Section: Resultsmentioning
confidence: 81%
“…The major advantage of the SL theory is that it is focused on individuals and their livelihoods instead of resources and their exhaustion. 37 Therefore, the model for this study was adopted from the empirical work of Ogundipe et al, 6 and the model assumed a linear relationship of the poverty (proxy for SDG 1) determinants in West Africa, which are specified in implicit form as:…”
Section: Methodsmentioning
confidence: 99%
“…In Pakistan, population growth has eroded fruits of higher economic growth. It is considered a cause for poverty [Mallick and Ghani (2005)].…”
Section: Data Sources and Research Methodsmentioning
confidence: 99%
“…Some researchers have pointed out several factors that can affect the PPP and HDI, including Grubaugh [29], who stated the variables that influence the growth of HDI in developing countries are population, population growth, and the initial level of the gross domestic product (GDP). Meanwhile, Mallick and Ghani [30] found that high population growth is the cause of poverty in Pakistan. While in North Sumatra Province, Indonesia, the GRDP and education level to university have a positive and significant influence in reducing the PPP [31].…”
Section: Data Applicationmentioning
confidence: 99%